2005
DOI: 10.1111/j.1600-0846.2005.00098.x
|View full text |Cite
|
Sign up to set email alerts
|

The hypomagnesic rat model: dermatitis‐prone hairless rats with mild magnesium depletion fed a diet low in lipids did not develop pruritic dermatitis

Abstract: The lipid-deficient diet was not able to induce pruritic dermatitis despite the fact that the rats were dermatitis prone because of mild magnesium depletion. It is not confirmed that dietary lipid depletion plays any significant role in the hypomagnesic dermatitis rat model. The dermatitis and the model appear to be strictly dependent on efficient magnesium depletion manufactured with very low magnesium levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…TRPM6 encodes transient receptor potential cation channel subfamily M member 6, a key regulator of cellular magnesium homeostasis 31,32 and relevant to pruritus. 33 From the patients' perspective, the improvement in itch after MSC infusion was a major health benefit, as noted previously in the pediatric population. 11 In contrast to pediatric studies, however, photographic documentation of wounds before and after MSCs showed highly variable responses, including no change or enlargement of individual wounds (Supplemental Fig 1).…”
Section: Discussionmentioning
confidence: 65%
“…TRPM6 encodes transient receptor potential cation channel subfamily M member 6, a key regulator of cellular magnesium homeostasis 31,32 and relevant to pruritus. 33 From the patients' perspective, the improvement in itch after MSC infusion was a major health benefit, as noted previously in the pediatric population. 11 In contrast to pediatric studies, however, photographic documentation of wounds before and after MSCs showed highly variable responses, including no change or enlargement of individual wounds (Supplemental Fig 1).…”
Section: Discussionmentioning
confidence: 65%
“…In rats, insufficient dietary magnesium intake leads to low serum Mg 2+ concentration which results in the development of dermatitis and intense scratching [374]. Likewise, pruritus of uremic patients completely disappeared after normalizing the concentration of magnesium Mg 2+ in the dialysate [375].…”
Section: Mg 2+ Homeostasis In Itch -Possible Roles Of Trpm6 and Trpm7mentioning
confidence: 96%
“…Mg 2+ , resulting in universal dermatitis and intense scratching behavior [217], it is tempting to ask whether a signaling dysfunction in the "magnesium -controlling" members of the TRPM…”
Section: Trpm6 and Trpm7 -Itch And The Magnesium Connectionmentioning
confidence: 99%